Cerebral Palsy - Clinical and Therapeutic Aspects 2018
DOI: 10.5772/intechopen.79452
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health in Children with Cerebral Palsy

Abstract: Cerebral palsy (CP) is a neurodevelopmental condition comprising a group of permanent disorders of movement and posture that are attributed to nonprogressive disturbances of the developing brain. The neuromuscular problems inherent in CP can affect oral health significantly in several ways. These can include changes in structure of the orofacial region, feeding problems, difficulties with maintaining oral hygiene; additionally, people with CP can encounter barriers in accessing oral health care. Several studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These results were in accordance with the study performed by Mutoh, et al, ( 2019), who stated that, hippo therapy was linked with improved cadence, step length, mean acceleration; stabilized displacement of patients; and positive relationship between the psychological status and QOL of the caregivers than those seen in the control group (p < 0.05). Also, consistent with the study done by Chang, et al, (2019) and Akhter, et al, (2018) who reported that, trained caregivers had positive effect on daily living skills of CP children and improvement of hygiene measures related to oral care.…”
Section: (Menlah Et Al 2020)supporting
confidence: 90%
“…These results were in accordance with the study performed by Mutoh, et al, ( 2019), who stated that, hippo therapy was linked with improved cadence, step length, mean acceleration; stabilized displacement of patients; and positive relationship between the psychological status and QOL of the caregivers than those seen in the control group (p < 0.05). Also, consistent with the study done by Chang, et al, (2019) and Akhter, et al, (2018) who reported that, trained caregivers had positive effect on daily living skills of CP children and improvement of hygiene measures related to oral care.…”
Section: (Menlah Et Al 2020)supporting
confidence: 90%
“…If dental erosions are observed in this group of patients, they should be referred to a gastroenterologist, and periodic examinations should be provided, and consumption of acidic beverages should be completely stopped for the health of soft tissues in the mouth. 9 Rieken et al 28 , stated that the reason for the…”
Section: % Of the Examined Children With Cp Use Regularmentioning
confidence: 99%
“…This effect limits the motor functions of the tongue, jaws, and orofacial muscles. 9 Dysfunction in the muscles also affects the salivary glands, causing a decrease in saliva production, which provides a basic protection against tooth decay. 10 In patients with CP, saliva production can sometimes be a contributing factor in easier chewing and swallowing of food.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, to identify the relationships between DMFTI and demographic data of children with CP, DMFTI and CP location, Silness-Loe plaque index and demographic data of children with CP, Silness-Loe plaque index, and CP location were other objectives. Many studies have been conducted worldwide regarding oral health status 7,8 and caregiver support of children with CP. 9 However, only one study was conducted on the prevalence of CP in Sri Lankan children, a descriptive cross-sectional study.…”
Section: Introductionmentioning
confidence: 99%